Two-dimensional WS2 nanoribbon deposition by conversion of pre-patterned amorphous silicon. (15th December 2016) - Heyne, Markus H; de Marneffe, Jean-François; Delabie, Annelies; Caymax, Matty; Neyts, Erik C; Radu, Iuliana; Huyghebaert, Cedric; De Gendt, Stefan
Abstract: We present a method for area selective deposition of 2D WS2 nanoribbons with tunable thickness on a dielectric substrate. The process is based on a complete conversion of a pre-patterned, H-terminated Si layer to metallic W by WF6, followed by in situ sulfidation by H2 S. The reaction process, performed at 450 °C, yields nanoribbons with lateral dimension down to 20 nm and with random basal plane orientation. The thickness of the nanoribbons is accurately controlled by the thickness of the pre-deposited Si layer. Upon rapid thermal annealing at 900 °C under inert gas, the WS2 basal planes align parallel to the substrate.